Three main metabolites from Wolfiporia cocos (F. A. Wolf) Ryvarden & Gilb regulate the gut microbiota in mice: A comparative study using microbiome-metabolomics - Lai, Yong; Yu, Hailun; Deng, Huiling; Fang, Qi; Lei, Hui; Liu, Li; Wu, Nannan; Guo, Xiurong; Song, Can (Frontiers in Pharmacology, 2022)
Poria cocos is an ancient edible and medicinal mushroom that has been valued for thousands of years for its tranquilising, diuretic, and spleen-enhancing properties. Because of the mushroom’s complex composition, its pharmacological effects have not been fully clarified. Therefore, to expand our knowledge of these effects from a pharmacological perspective, we extracted three major components of P. cocos, including water-soluble polysaccharides (PCX), water-insoluble polysaccharides (PCY), and triterpenoid saponins (PCZ) for intragastric injection into healthy mice. These injections were made to explore the component’s effects on the mice’s gut microbiota and their metabolomics. The microbiota analysis showed that the three major components successfully remodeled the gut microbiota by altering its composition and structure, and PCY had the strongest effect in regulating gut microbiota through increasing the number of Lactobacillus. The metabolomic results showed that all three major active ingredients caused different degrees of alterations in gut metabolites. In conclusion, our study further investigated the pharmacological functions of P. cocos, and revealed the differing effects of its three major components on gut microbiota. The results suggested that PCY is a prominent prebiotic, and provided us with new insights into the potential development of fungal polysaccharides in Chinese traditional medicine.